An Overview of Entrepreneurship Education - Paul Jones (Systemic Entrepreneurship: Contemporary Issues and Case Studies, 2015)
There has been a significant global growth in entrepreneurship education within the university sector in the last two decade owing to its potential social, economic and educational benefits. However, there remains a longstanding debate within the university sector regarding the effectiveness of entrepreneurship education and further evidence is required to confirm both best practice and its actual impact in terms of enabling entrepreneurial activity. This chapter seeks to inform this debate. While the key academic literature has been drawn from a largely USA and European context it is refreshing to see a new evidence base emerging from an African context. All the papers within this chapter are drawn from the pedagogical experience and projects in an African context.